An Approach to the Performances Antivisita and Cuarto Intermedio Produced by Child Victims of Argentine State Terrorism - Hassid, Mora (2025)
The present paper analyzes two performances made by child victims of state violence in Argentina: Cuarto intermedio: guía práctica para audiencias de lesa humanidad (2018) by Mónica Zwaig and Félix Bruzzone, and Antivisita: formas de entrar y salir de la ESMA (2022) by Mariana Eva Pérez and Laura Kalauz. The paper claims that both theatrical plays evoke two realms of memory, in Pierre Nora’s terms, related to a moment in Argentinian history in which the state reviews recent history from a memorial perspective. Each performance evokes a realm of memory related to that period: the creation of sites of memory and the re(opening) of court cases. Both plays evoke these realms of memory, but transform the usual shapes of these devices. Also, the two plays incorporate the spectator as a performer in the play: the performances not only aim to an emancipated spectator, in Rancière’s terms, but they also include the body of the spectator as part of the performance. The article analyzes the spectator in each performance and argues that both plays propose a way of transmission of memory that has the body of both performers and spectators as protagonists.